Which Dimensions Are Related to Populist Attitudes: An Educational View Based on a Systematic Literature Review - Ricardo Soares; Carla Malafaia; Pedro D. Ferreira (Societies)
In the last decade, we have witnessed increasing knowledge production on populism at the level of individuals. However, the systematization of these studies’ conclusions is still scarce. There is also little research on the relationship between populism and education. Based on a systematic literature review, this article contributes to this by first focusing on what studies have revealed about the relationship between populist attitudes and socioeconomic, political, emotional characteristics and media-related preferences. Based on predefined criteria and a double-screening process, our literature search led to the selection of 68 studies focused on populist attitudes. The analysis of these articles enables us to understand that populist attitudes (i) are influenced by socioeconomic characteristics; (ii) have a nuanced relationship with politics; (iii) are driven by emotional dimensions; and (iv) are associated with diverse views about the media and media consumption preferences. We discuss the main findings of this systematic literature review and point out possible educational responses to individual populist standpoints according to their various causes, particularly in terms of the role of political and media education.